Failures in periodontal therapy - Jithendra, KD; Bansali, A; Ramachandra, SS (Bangladesh Journal of Medical Science, 2010)
Studies have shown that modern periodontal therapies are effective in maintaining a healthy natural dentition as well as controlling periodontal disease. Numerous treatment strategies and various techniques have been designed & described to treat periodontal disease. Most of these procedures had drawbacks which were identified, leading to the modifications of the original techniques which lead to better treatment options, but still very less emphasis has been laid on failures. Without a regular program of clinical re-evaluation, plaque control, oral hygiene instructions, and reassessment of biomechanical factors the benefits of treatment are often lost and inflammatory disease in the form of recurrent periodontitis may result. So, this review describes the most common failures noticed in periodontal therapies and also discusses the possible solutions to reduce the incidence of failures in periodontal therapy. Key words: Periodontal therapy; risk factors; failures. DOI: 10.3329/bjms.v9i4.6680 Bangladesh Journal of Medical Science Vol.09 No.4 July 2010 pp.193-198